Why it is important to precisiate goals - Kosheleva O. (2017)
© 2016 World Academic Press, UK. All rights reserved. After Zadeh and Bellman explained how to optimize a function under fuzzy constraints, there have been many successful applications of this optimization. However, in many practical situations, it turns out to be more efficient to precisiate the objective function before performing optimization. In this paper, we provide a possible explanation for this empirical fact.